2018
DOI: 10.1016/j.ijscr.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of a balloon dilatation catheter to enable mechanical lithotripsy of difficult common bile duct stones after initial failed attempt: A case report

Abstract: HighlightsNovel technique for increasing working space in the common bile duct.May enable endoscopists to re-attempt mechanical lithotripsy after initial failed attempt.If successful, will decrease number of procedures patient has to undergo.Should be used only by advanced endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…No perforation was observed in patients dilated from 12 to 15 mm [16] and in our technique, we never dilate >15 mm. The presence of a stone could increase the risk of perforation, but this was not observed in our study as well as in the one by Park et al [9] and 2 other case reports [7, 8]. We presume that harder stones, especially some cholesterol stones originated in the gallbladder, pose an extra perforation risk due to the fact that in large balloon lithotripsy, the stone is pressed against the bile duct wall and the wall in contact with the balloon or the stone may rupture.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…No perforation was observed in patients dilated from 12 to 15 mm [16] and in our technique, we never dilate >15 mm. The presence of a stone could increase the risk of perforation, but this was not observed in our study as well as in the one by Park et al [9] and 2 other case reports [7, 8]. We presume that harder stones, especially some cholesterol stones originated in the gallbladder, pose an extra perforation risk due to the fact that in large balloon lithotripsy, the stone is pressed against the bile duct wall and the wall in contact with the balloon or the stone may rupture.…”
Section: Discussioncontrasting
confidence: 72%
“…Park et al [9] were the first to report the use of large balloon lithotripsy in 7 patients with giant or impacted stones with full success and no complications. Loh et al [7] reported a single case of large balloon lithotripsy in order to produce working space for the deployment of the basket. It must be emphasized that cholangioscopy-guided laser or electro-hydraulic lithotripsy also has a stone clearance rate of approximately 70–90%, requires 1 to 2 sessions beyond the index ERCP, and is also not a complication-free procedure, especially with an increased cholangitis rate, although perforations or bleeding, due to the lithotripsy method, could very rarely occur [2, 4, 12, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERCP failure to extract stones may be due to failed cannulation (i.e., Juxta-papillary diverticulum, intra-diverticular papilla or small papilla), or failed extraction [ [35] , [36] , [37] , [38] , [39] ]. The failed extraction occur with difficult stones (i.e Mirrizi's syndrome, stricture of the lower CBD, impacted, large (<15 mm), multiple (<3), or intrahepatic duct/cystic duct stones), especially when using standard methods (balloon or basket after ES or endoscopic papillary balloon dilatation (EPBD)) [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%